Metagenomic Detection of Multiple Viruses in Monk Parakeet (Myiopsitta monachus) in Australia - Babu Kanti Nath; Suman Das Gupta; Saranika talukder; Nasrin Sultana Tonu; Shane R. Raidal; Jade K. Forwood; Subir Sarker (Veterinary Medicine and Science)
ABSTRACT Background Birds are known to harbour many pathogens, including circovirus, herpesviruses, adenoviruses and Chlamydia psittaci. Some of these pose zoonotic risks, while others, such as beak and feather disease virus (BFDV), have a significant impact on the conservation of endangered bird species. Objectives This study was aimed to determine the faecal virome of a group of apparently healthy Monk parakeet using high‐throughput sequencing. Methods Fresh faecal samples were collected from four Monk parakeets at a pet shop in Melbourne, Australia. Virus enrichment and nucleic acid extraction were performed on the faecal samples, followed by high‐throughput sequencing at the Australian Genome Research Facility (AGRF). Results Utilising an established pipeline for high‐throughput sequencing data analysis, this study revealed the presence of three viruses of the families Circoviridae, Parvoviridae and Adenoviridae. Subsequent sequence comparison and phylogenetic analyses further confirmed that the detected viruses belong to the genera Chaphamaparvovirus (unassigned species), Circovirus (species Circovirus parrot) and Siadenovirus (species Siadenovirus viridis). Conclusion Despite non‐pathogenicity, the existence of multiple viruses within a bird species underscores the risk of these viruses spreading into the pet trade. Detection and a better understanding of avian viruses are crucial for the establishment of appropriate management and biosecurity measures in the domestic and international bird trade, which ultimately supports the conservation of vulnerable bird species.